2007
DOI: 10.1007/s11426-007-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Research of the relationship of intracellular acidification and apoptosis in Hela cells based on pH nanosensors

Abstract: In this paper, the relationship of intracellular acidification and apoptosis in Hela cells induced by vincristine sulfate has been studied by use of the ratiometric pH nanosensors that have been developed by our group, employing fluorescein isothiocyanate (FITC) doped as the pH-sensitive dye and Tris(2,2'-bipyidyl) dichlororuthenium(II) hexahydrate (RuBpy) doped as reference dye. The pH change of the Hela cells induced by vincristine sulfate has been monitored in vivo, in situ and real time by use of the ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Both lysosomal pH changes in murine macrophages stimulated by chloroquine and the intracellular acidification in apoptotic cancer cells were monitored in real time and with high pH sensitivity. Furthermore, the relationship of intracellular acidification and apoptosis in HeLa cells induced by vincristine sulfate was studied with this ratiometric pH nanosensors, which revealed that apoptosis was preceded by intracellular acidification . These results would provide theoretical foundation for the therapy of cancer through the interference of cells’ pH by use of vincristine sulfate or other anticancer drugs.…”
Section: Functionalized Sinps For Fluorescence Imaging At Cellular An...mentioning
confidence: 86%
See 1 more Smart Citation
“…Both lysosomal pH changes in murine macrophages stimulated by chloroquine and the intracellular acidification in apoptotic cancer cells were monitored in real time and with high pH sensitivity. Furthermore, the relationship of intracellular acidification and apoptosis in HeLa cells induced by vincristine sulfate was studied with this ratiometric pH nanosensors, which revealed that apoptosis was preceded by intracellular acidification . These results would provide theoretical foundation for the therapy of cancer through the interference of cells’ pH by use of vincristine sulfate or other anticancer drugs.…”
Section: Functionalized Sinps For Fluorescence Imaging At Cellular An...mentioning
confidence: 86%
“…Furthermore, the relationship of intracellular acidification and apoptosis in HeLa cells induced by vincristine sulfate was studied with this ratiometric pH nanosensors, which revealed that apoptosis was preceded by intracellular acidification. 45 These results would provide theoretical foundation for the therapy Since functionalized SiNPs could enter into cells and locate in some certain organelles, they could also be utilized by nanoparticle-based controlled release systems for intracellular drug delivery and therapy studies. In order to increase the drug load amount, mesoporous SiNPs were selected to fabricate stimuli-responsive intracellular controlled release systems.…”
Section: Functionalized Sinps For Fluorescencementioning
confidence: 99%
“…We have developed uniform biofunctionalized core/shell NPs, composed of a functionalized fluorescent or magnetic core, a modifiable coating shell, and the biomolecules modified on the surface of the nanoparticles, as shown in Figure 8. The three parts all prominently contribute to their application of biomedicine, such as cell staining [92][93][94][95][96][97][98][99][100][101][102], bacteria detection [103,104], nanosensing [105,106], biomolecule detection and separation [107][108][109][110][111], gene and drug delivery [112][113][114][115][116], and biotechnological application in DNA protection [117]. Here, a few applications for protein detection and separation using biofunctionalized nanoparticles are discussed.…”
Section: Protein Analysis Based On Biofunctionalized Nanoparticlesmentioning
confidence: 99%